Optimasi Kekasaran Permukaan Proses Pembubutan Baja ST.42 Dengan Menggunakan Metode Taguchi - Said Apreza; Zaldy Kurniawan; Muhammad Subhan (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
Minimal surface roughness value is the performance to be achieved in the process of CNC NLX 2500, is necessary to regulate variables NLX 2500 CNC process in order to obtain the proper response surface roughness of the workpiece is minimal.research that has been done is to determine the contribution of these variables NLX CNC process in 2500 to reduce the variation of the response surface roughness of the workpiece simultaneously. Moreover, it also made the determination that the proper setting of the variables NLX2500 CNC process in order to obtain the surface roughness of the workpiece is minimal.machining process variable is varied spindle rotation, motion eat, and in the funeral. The experimental design is determined based on the Taguchi method and form of orthogonal L9 (33). Optimization method is used Taguchi. The randomized trial with replication 2 times to overcome interference factors that occur during the machining process.the results showed that to reduce the variation of the response simultaneously, eat motion has the largest percent of the contribution, which amounted to 99.48%, spindle rotation has a percent contribution of 0.0974%, the feeds have a percent contribution of -0.126%.to obtain a surface roughness of the workpiece is minimal, spindle rotation is set at 2748 rpm, eating motion is set at 0.15 mm / rotation, the funeral was adjusted to 0.5 mm.